Extra-adrenal glucocorticoids and mineralocorticoids: evidence for local synthesis, regulation, and function - Taves, Matthew D.; Gomez-Sanchez, Celso E.; Soma, Kiran K. (American journal of physiology: endocrinology and metabolism, 2011)
Glucocorticoids and mineralocorticoids are steroid hormones classically thought to be secreted exclusively by the adrenal glands. However, recent evidence has shown that corticosteroids can also be locally synthesized in various other tissues, including primary lymphoid organs, intestine, skin, brain, and possibly heart. Evidence for local synthesis includes detection of steroidogenic enzymes and high local corticosteroid levels, even after adrenalectomy. Local synthesis creates high corticosteroid concentrations in extra-adrenal organs, sometimes much higher than circulating concentrations. Interestingly, local corticosteroid synthesis can be regulated via locally expressed mediators of the hypothalamic-pituitary-adrenal (HPA) axis or renin-angiotensin system (RAS). In some tissues (e.g., skin), these local control pathways might form miniature analogs of the pathways that regulate adrenal corticosteroid production. Locally synthesized glucocorticoids regulate activation of immune cells, while locally synthesized mineralocorticoids regulate blood volume and pressure. The physiological importance of extra-adrenal glucocorticoids and mineralocorticoids has been shown, because inhibition of local synthesis has major effects even in adrenal-intact subjects. In sum, while adrenal secretion of glucocorticoids and mineralocorticoids into the blood coordinates multiple organ systems, local synthesis of corticosteroids results in high spatial specificity of steroid action. Taken together, studies of these five major organ systems challenge the conventional understanding of corticosteroid biosynthesis and function.